Correspondent's Report: Recent Work in Philosophy II - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Correspondent's Report: Recent Work in Philosophy II." Artificial Intelligence 22 (1984): 231-34.